Increased expression of urokinase plasminogen activator in Quebec platelet disorder is linked to megakaryocyte differentiation - Veljkovic, D. Kika (American Society of Hematology, 2009)
Quebec platelet disorder (QPD) is an inherited bleeding disorder associated with increased urokinase plasminogen activator (uPA) in platelets but not in plasma, intraplatelet plasmin generation, and α-granule protein degradation. These abnormalities led us to investigate uPA expression by QPD CD34(+) progenitors, cultured megakaryocytes, and platelets, and whether uPA was stored in QPD α-granules. Although QPD CD34(+) progenitors expressed normal amounts of uPA, their differentiation into megakaryocytes abnormally increased expression of the uPA gene but not the flanking genes for vinculin or calcium/calmodulin-dependent protein kinase IIγ on chromosome 10. The increased uPA production by cultured QPD megakaryocytes mirrored their production of α-granule proteins, which was normal. uPA was localized to QPD α-granules and it showed extensive colocalization with α-granule proteins in both cultured QPD megakaryocytes and platelets, and with plasminogen in QPD platelets. In QPD megakaryocytes, cultured without or with plasma as a source of plasminogen, α-granule proteins were stored undegraded and this was associated with much less uPA-plasminogen colocalization than in QPD platelets. Our studies indicate that the overexpression of uPA in QPD emerges with megakaryocyte differentiation, without altering the expression of flanking genes, and that uPA is costored with α-granule proteins prior to their proteolysis in QPD.